PENGARUH DISIPLIN KERJA,MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJAPEGAWAI KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) SOLOK SELATAN - Tomi Rivaldo; Juarsa Badri; Elva Dona (LP2M Universitas Bina Bangsa, 2024)
This study aims to examine work discipline on employee performance, to test work motivation on employee performance, to test job satisfaction on employee performance. This research was conducted at the Solok Selatan Office of the Personnel and Human Resources Development Agency (BKPSDM). Type in this study using Quantitative. Sampling method using a saturated total sampling of 42 samples. The data analysis technique used is validity, reliability, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and t test. The results showed that work discipline has a positive and significant effect on employee performance. work motivation has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance. So it can be concluded that work discipline is accepted, work motivation is accepted and job satisfaction is accepted